The effect of excercise and pioglitazone on the dynamic responses of oxygen uptake and leg vascular conductance in males with type 2 diabetes - O'Connor, Eamonn (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
The exercise capacity of an individual with T2D is often reduced due to the effects of T2D upon oxygen consumption- (VO2) and vascular conductance (VC)- kinetics. Exercise training has been shown to induce improvements in the V O2-kinetic and the VC-kinetic responses of individuals with T2D. Rosiglitazone use in T2D has resulted improvements in V O2peak in individuals with T2D, although it did not result in improvements in V O2 kinetics. However, no study has yet investigated the effects of treatment with pioglitazone (PIO) on measures of V O2peak, VO2 kinetic or VC kinetic responses. It has been shown that treatment with PIO induces similar effects on endothelial function as rosiglitazone, therefore PIO treatment may induce similar improvements in exercise performance.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin.